Exercise and cancer: from “healthy” to “therapeutic”? - Idorn, Manja (Cancer Immunol Immunother, 2017)
Exercise improves functional capacity and patient-reported outcomes across a range of cancer diagnoses. The mechanisms behind this protection have been largely unknown, but exercise-mediated changes in body composition, sex hormone levels, systemic inflammation, and immune cell function have been suggested to play a role. We recently demonstrated that voluntary exercise leads to an influx of immune cells in tumors, and a more than 60% reduction in tumor incidence and growth across several mouse models. Given the common mechanisms of immune cell mobilization in mouse and man during exercise, we hypothesize that this link between exercise and the immune system can be exploited in cancer therapy in particular in combination with immunotherapy. Thus, we believe that exercise may not just be “healthy” but may in fact be therapeutic.